La inexistencia de normas de normas especificas asistenciales vulnera los derechos de niños, niñas y adolescentes. - Ledesma Isquierdo, Katty Yadira (2013)
This thesis, whose theme is “The lack of care specific rules violates the rights of children and adolescents “, consists of 6 chapters in which the subjects are detailed about the lack of care measures for children, and adolescents. In the introduction, a summary of the lack of care measures for children and adolescents, on the critical blocks, the reality of the lack of assistance measures by the State to children and adolescents focuses, noted the general and specific objectives, hypothesis, independent and dependent variables and resources are detailed. In the theoretical framework, background, rationale, Doctrine, Jurisprudence, Law and Comparative Law from the object of study focuses. In the methodology , the methods used are determined , the techniques applied in the field , the application of surveys to citizens of Canton Quevedo, and lawyers in free practice , the interview with such results tabulation was performed , processing and analysis and interpretation of data , report research and hypothesis testing was developed. Detailed conclusions ie that there are no welfare measures and violating the rights of children and adolescents due to lack of specific rules. Recommendations must say that it must create rules that benefit in children and adolescents. The proposed legal reform to art. 205 of the Code on Children and Adolescents, prioritizes assistance to children and adolescent.